2017
DOI: 10.1016/j.brainres.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of c-Fos induction in response to social interaction in male and female Fisher 344 rats

Abstract: Sex differences in the expression of social behavior are typically apparent in adolescent and adult rats. While the neurobiology underlying juvenile social play behavior has been well characterized, less is known about discrete brain regions involved in adult responsiveness to a same sex peer. Furthermore, whether adult males and females differ in their responsiveness to a social interaction in terms of neuronal activation indexed via immediate early gene (IEG) expression remains to be determined. Thus, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…Here, although both males and females exhibited increased social interaction-induced c-fos expression after PSI, MJN110 significantly reduced social interaction-induced c-fos only in females. It has previously been reported that females engage in more social interaction than males (Perkins et al 2017), consistent with the current findings, and in that study social interaction-induced c-fos was greater in the mPFC of females than males (Perkins et al 2017). Sex differences in the effects of cannabinoid manipulations have also been previously reported.…”
Section: 0 Discussionsupporting
confidence: 93%
“…Here, although both males and females exhibited increased social interaction-induced c-fos expression after PSI, MJN110 significantly reduced social interaction-induced c-fos only in females. It has previously been reported that females engage in more social interaction than males (Perkins et al 2017), consistent with the current findings, and in that study social interaction-induced c-fos was greater in the mPFC of females than males (Perkins et al 2017). Sex differences in the effects of cannabinoid manipulations have also been previously reported.…”
Section: 0 Discussionsupporting
confidence: 93%
“…Specifically, in Sprague Dawley rats, adult males exhibit greater levels of social behavior relative to females (Stack et al, 2010; Varlinskaya et al, 2014). In contrast, adult female F344 rats exhibit greater levels of social investigation relative to adult male F344 rats (Perkins et al, 2017). This is consistent with the hypothesis that increased number and/or activation of microglia, such as what was observed in the MEA here might adversely influence the expression of social behavior.…”
Section: 0 Discussionmentioning
confidence: 96%
“…The PVN receives substantial brainstem inputs and as such is a key site of integration of ascending signals and the neuroendocrine responses to stress (Myers et al, 2017; Pacak and Palkovits, 2001). The BNST is involved in social recognition (Dumais et al, 2016b) and exhibits sex-specific patterns of immediate early gene (c-Fos) activation following a social experience (Perkins et al, 2017). The amygdala has been implicated in social information processing in humans (Adolphs, 2003) and the MEA specifically exhibits induction of c-Fos in response to social interaction in adult rats that is blunted in aged rats (Salchner et al, 2004).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Given our previous findings of age and/or sex differences in the social interaction test (Perkins et al, 2017, 2016), we first assessed social investigation and contact behavior exclusively in the saline vehicle group. Aging rats had significantly lower social investigation [F(1,37) = 38.44, p < 0.00001] and social contact behavior [F(1,37) = 11.05, p = 0.002] relative to their adult counterparts, whereas no sex differences were evident in either dependent measure (Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Social interaction testing occurred in custom-made Plexiglas® chambers lined with clean pine shavings (45 × 30 × 30 cm). Each chamber was divided into two equally sized compartments separated by a clear Plexiglas® partition with an aperture (9 × 7 cm) that allowed the rats to move freely between compartments (Perkins et al, 2017). Males and females were tested in separate rooms with dim lighting (10–20 lux) between 0800 and 1300.…”
Section: Methodsmentioning
confidence: 99%